Kekuatan Mengikat Akta Perdamaian (Acte Van Dading) Yang Dibuat Diluar Pengadilan Yang Isinya Berbeda Dengan Putusan Yang Sudah Berkekuatan Hukum Tetap (In Kracht Van Gewijsde) - Mukti, Dhimas Haris Anggara (Jurnal Hukum & Pembangunan, 2023)
This article discusses the legal force of peace deeds (acte van dading) made outside of court which contents are different from a legally binding decision (in kracht van gewijsde). The research used as writing material is research using philosophical approaches, normative juridical methods and literature review, which is carried out by examining library materials or secondary data. The results of the research conclude that a peace agreement is valid according to law if it meets the requirements set out in statutory regulations, either in the form of a private agreement or an authentic deed, which will have power for the parties who make it and apply as law to end a case. who is dependent. The legal force of a peace agreement made outside of court is recognized by law and can be stated in a peace deed (acte van dading) as long as it meets the requirements by filing a lawsuit. The legal force of a peace agreement made after a court decision at the first instance is recognized by law and can be included in a peace deed (acte van dading) as long as it meets the requirements by submitting it to the case examining judge at the legal remedy level.